IMPLEMENTASI KEBIJAKAN ALOKASI DANA GERAKAN DESA MEMBANGUN DI KECAMATAN BAHAU HULU KABUPATEN MALINAU PROVINSI KALIMANTAN UTARA - Victor Romawan (Jurnal Paradigma (JP), 2019)
The purpose of this research is to know how Implemntasi Fund Allocation of Village Movement Build in Village of sub-district of Bahau Hulu. The research method used is descriptive method with qualitative analysis. The results of the study show that Implementation of Gerdema Fund Allocation in Upper Bahau Subdistrict 2016, the average absorption of funds under 70% (Seventy Percent), allocation targets and Gerdema not exactly as specified in the Regulation of Malinau Regent number 3 of 2016. Keywords: Gerdema, Fund Allocation, Implementation